Narrative resourses of inquiry into female identity and recurrent topics in the literature of María Luisa Bombal, Flora Yáñez and María Carolina Geel - Suárez Hernán, Carolina (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Novels written by women in Chile underwent an important development between 1930 and 1960. This article aims to contribute to the actual recovery of feminine narrative through the analysis of some novels published by María Luisa Bombal, Flora Yáñez, María Carolina Geel y Chela Reyes. Our work will focus on establishing links among these novels and remark recurring symbols and topics. Also, the article analyzes narrative strategies to create feminine characters and focuses on way of express subjectivity.
Keywords: narrativa femenina chilena, María Luisa Bombal, Flora Yáñez, María Carolina Geel.